Proses Penyelesaian Perkara Pelanggaran Lalu Lintas Yang Dilakukan Oleh Prajurit TNI-AD di Wilayah Hukum Pengadilan Militer III-15 Kupang - Morynda Livia Ester Kadek; Simplexius Asa; A. Resopijani (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
A traffic violation is an act or action carried out by a person driving a motorized vehicle or a pedestrian which is contrary to the laws and regulations in the field of traffic and road transportation. Therefore, traffic management and engineering is needed so that every motorized vehicle user has regulations in traffic so that they understand the use of road directions and lanes and the law is a guide to the rules and regulations of a society and must be obeyed. The main problems in this research are: (1) What is the process for resolving traffic violation cases committed by TNI-AD soldiers in the Legal Area of ​​Military Court III-15 Kupang? (2) How are criminal sanctions imposed on TNI-AD soldiers who commit traffic violations in the Legal Area of ​​Military Court III-15 Kupang?. This research is empirical normative research, so the data sources used are primary data sources, secondary data and tertiary data. Primary data was obtained from interviews, secondary data was obtained from libraries, journals and the internet, and tertiary data was obtained from dictionaries, Wikipedia and encyclopedias. Data were analyzed descriptively-qualitatively. The results of this research show that (1) The process of resolving cases of road traffic violations committed by the TNI-AD was examined using a rapid examination process based on Law Number 31 of 1997 concerning Military Justice and Law Number 22 of 2009 concerning Traffic and Transport Roads. (2) The criminal sanctions imposed on the TNI-AD who commit traffic violations are fines and imprisonment.